MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS X MA MUHAMMADIYAH 2 AL FURQAN MELALUI MODEL PEMBELAJARAN PENEMUAN TERBIMBING - Ahmad Sudrajat; Zainuddin Zainuddin; Misbah Misbah (Jurnal Ilmiah Pendidikan Fisika, 2017)
Low mastery of science process skills indirectly affect student learning outcomes. Therefore, research that aims to improve students' science process skills. The subjects were students of class X MA Muhammadiyah 2 Al Furqan. This research is a classroom action research that specifically aims to describe: (1) the implementation of lesson plan during the learning proses by using guided discovery learning model, (2) an increase in students 'science process skills, and (3) the results of students' learning product. The subjects were students of class X MA Muhammadiyah 2 Al Furqan. Data collection techniques using observation, testing, and documentation for research activities in class X MA Muhammadiyah 2 Al Furqan. The results showed that the guided discovery learning model can improve: (1) the implementation of lesson plan during the learning proses by using guided discovery learning model during each cycle is very good, (2) science process skills of students increased in each cycle with all aspects have achieved both categories at the end of the third cycle, (3) mastery learning outcomes of the classical product the students in each cycle has increased. Thus be concluded that the application of guided discovery learning model by maximizing each phase in the material temperature and heat can enhance science process skills of students of class X MA Muhammadiyah 2 Al Furqan.